TINGKAT RETENSI TAMU: TINGKAT RETENSI TAMU - Michelle Vireal Gift Kowaas; Maryke Alelo; Pearl Loesye Wenas (Jurnal Pariwisata Tawangmangu, 2026)
Guest retention rate refers to hotel’s industy capability to maintain customer’s and embolden repeat visit. This study aims to analyze the guest retention rate and the factors influencing it at Roger’s Hotel Manado. The research subjects focuses on hotel guests who have stayed in Roger’s Hotel Manado since 2025. This study employs a qualitative approach using in-depth interviews and secondary data taken from all front office. The collected data is analyzed using thematic analysis to identify patterns and meanings related to guest retention. The results indicate that service quality, especially in terms of friendliness, responsiveness, and attention to guest needs, plays a significant role in improving guest retention. In addition, positive stay experiences and guest satisfaction are key factors that encourage repeat visits. Therefore, consistently improving service quality can strengthen guest loyalty and increase the likelihood of return visits.